Systems Analysis & Design in a Changing World - Satzinger, John W. Burd, Stephen D. and Jackson, Robert B. (Canada Thomsan, 2007)
Building on its continued success this text has been revised to provide the most comprehensive, balanced and up-to-date coverage of systems analysis and design available. The Fourth Edition maintains the dual focus on the concepts and techniques from both the traditional, structured approach and the object-oriented approach to systems development. Instructors have the flexibility to emphasize one approach over the other, or both, while referring to one integrated case study that runs through every chapter.
Includes Index and Colored Illustrations.
Keywords: System design -- System analysis